Disbursement of Tax Arrears: Active Tax Collection and Tax Audit on Corporate Taxpayers - Ristiyana, Rida; Atichasari, Anna Sofia; Dahliana, Dahliana; Erwindiawan, Erwindiawan (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study aims to determine the effect of warning letters, forced letters, and confiscation letters on the disbursement of tax arrears with tax audit as a moderation variable. The type of research is quantitative using secondary data with indirect data collection techniques. The population in the study is corporate taxpayers registered at KPP Pratama Tigaraksa. The sampling technique uses purposive sampling. The data analysis method uses panel data through Eviews 10. The results of the parsial of the warning letter had a positive and significant effect on the disbursement of tax arrears, forced letter and confiscation letter had no effect on the disbursement of tax arrears and the results of the MRA tax audit could not moderate the disbursement of tax arrears. The results of this study simultaneously warning letter forced letter, and confiscation letter have an effect on the disbursement of tax arrears. The latest in this study is to add tax audits as a moderation variable with different objects at KPP Pratama Tigaraksa. This research has implications to increase taxpayer awareness in fulfilling tax obligations and assist the Directorate General of Taxes in decision-making policies related to the renewal of active tax collection regulations.